2017
DOI: 10.1002/jcb.26370
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits osteoclastogenesis through modulation of helper T cells‐secreted IL‐4

Abstract: Naringenin (NAR) is a natural predominant flavanone and has a wide range of pharmacological activities. The aim of this study was to investigate the protective mechanisms of NAR on RANKL-induced osteoclastogenesis and osteoclast bone resorption. T cells were divided into four groups under different concentrations of NAR (0, 25, 50, 100 µM). CD4 T cell subsets in different groups were evaluated by flow cytometry. TRAP staining, pit formation assays and F-actin ring immunofluorescent staining were performed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In addition, naringenin improves osteogenic differentiation of rat BMSCs and hPDLSCs through SDF-1/CXCR4 signaling pathway ( Zhang L. et al, 2021 ; Wang et al, 2021 ). Wang et al reported that naringenin impedes osteoclast differentiation by the inhibition of p38 signaling and enhancing helper T cells-secreted IL-4 ( Wang et al, 2014 ; Wang et al, 2018 ). In this study, we confirmed naringenin treatment promoted osteoblastic differentiation of mice BMSCs in vitro and the best concentration was around 10–15 μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, naringenin improves osteogenic differentiation of rat BMSCs and hPDLSCs through SDF-1/CXCR4 signaling pathway ( Zhang L. et al, 2021 ; Wang et al, 2021 ). Wang et al reported that naringenin impedes osteoclast differentiation by the inhibition of p38 signaling and enhancing helper T cells-secreted IL-4 ( Wang et al, 2014 ; Wang et al, 2018 ). In this study, we confirmed naringenin treatment promoted osteoblastic differentiation of mice BMSCs in vitro and the best concentration was around 10–15 μM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some pioneer studies illustrated the beneficial effects of naringenin on bone diseases such as chronic arthritis and osteoporosis ( Kaczmarczyk-Sedlak et al, 2016 ; Manchope et al, 2018 ). Naringenin could promote osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) and suppress osteoclastogenesis through enhancement of helper T-cell-secreted IL-4 ( Wang et al, 2018 ; Zhang L. et al, 2021 ; Wang et al, 2021 ). However, most of these studies do not supply high-quality data of naringenin’s effects in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Primary cultures of DRG neurons from adult female SD rats (pathogen-free; 140–160 g; Envigo) were made. ,,,,,, Naringenin treatment was applied overnight at 100 μM using 0.1% DMSO as a vehicle control. While relatively high, a concentration of 100 μM naringenin has been previously reported to be needed to detect biological effects including neuroprotection against LPS-induced dopamine neurotoxicity, inhibition of osteoclast formation, induction of anion transport across the rat colonic mucosa, caspase-3 activity in neutrophils, or suppression of prostate tumor cell proliferation . The next day, cultures were analyzed by whole cell patch clamp to measure Ca 2+ and Na + currents exactly as before. , Recordings were all obtained from small-diameter DRG neurons (size of ∼20 μm ± 2).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was found that naringenin exerted its protective effects by inhibiting osteoclastogenesis and osteoclast bone resorption [19,20]. Therefore, naringenin might have therapeutic potentials for a range of bone diseases such as osteoporosis, repairing of bone defects, alveolar bone resorption and other.…”
Section: Discussionmentioning
confidence: 99%
“…1), widely present in fruits such as orange, pomelo, and drynaria, is a dihydro-flavonoid compound that shows chemotactic activity [11] and other biological effects such as anti-inflammatory, antioxidative, anticancer and antiadipogenic activities [12][13][14][15], and was also shown to have anti-osteoporotic and anti-osteolytic effects [16]. Several experiments have shown that naringenin could reduce the osteolytic activities of osteoclasts, and improve the osteogenic differentiation and mineralization effects of the osteoblasts in osteolysis-related diseases [16][17][18][19][20]. The aim of the study was to investigate the effect of naringenin on the osteogenic differentiation of BMSCs and its role in the SDF-1/CXCR4 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%